Zmiany kondycji fizycznej polskiej młodzieży w ciągu ostatnich dekad - Ryszard Przywęda (Studia Ecologiae et Bioethicae)
Physical development, rate of sexual maturation, physical fitness, working capacity and general wellbeing of the organism are the main criteria of the health status of children and youth. The cross-sectional studies were organized in ten-year-intervals in the randomly selected Polish schools representing the whole nation. The studies took place in 1979, 1989 and 1999 and included children and youth aged 7-19 years. The results demonstrate the continuous positive secular trend showing more intensive physical growth and earlier maturation. These observations give the evidence of a rather good health status of the present young generation. However, changes in the level of physical fitness and working capacity of youth present the decreasing tendency during this 20-year-period. The changes in motor performance are better indicator of the general health status than the rate and level of physical development. The results of this paper show the picture of so called “opening scissors”, which means that even though the children and youth in 1999 were better physically developed (taller and heavier) than children studied in 1999 and 1989, their motor abilities were showing the gradual decrease during this period of time. The possible causes of this event have been presented and discuss in this paper.